Effect of geographical location, insect type and cooking method on the nutritional composition of insects consumed in South Africa - Hlongwane, Z T; Siwela, M; Slotow, R; Munyai, T C (Journal of insects as food and feed, 2022)
Edible insects may be a sustainable source of protein and some other nutrients, especially for low-economic-status communities. The current study determined the influence of insect type, geographic location, and cooking method on the nutritional composition of insects. The investigation would contribute to the maximal derivation of the nutritional benefits of insects. Dried samples of four insect types, (mopani worm), caterpillar, termite soldiers/workers, and termite alates, were procured from different street vendors across Vhembe district in Limpopo Province, South Africa. samples were cooked by frying, boiling with and without salt addition. Generally, nutrient content varied significantly with insect type and geographic location (p<0.05). Protein content varied from 40 g/100 g in termite alates to 69.75 g/100 g in termite soldiers/workers. Termite soldiers/workers had the highest iron content (range: 545-629.5 mg/kg), whilst caterpillar had the highest zinc content (range: 122.14-150.33 mg/kg). Similarly, caterpillar had the highest levels of lysine (range: 0.80-4.53 g/100g), threonine (range: 0.79-2.64 g/100g) and isoleucine (range: 0.63-2.33). On the other hand termite soldiers/workers had the highest levels of valine (range: 2.20-3.47 g/100g), leucine (range: 2.49-3.87 g/100g) and phenylalanine (range: 1.38-3.55 g/100g). Cooking method significantly affected nutrient retention. Boiling with salt added resulted in the highest retention of protein and total mineral content (ash), and, therefore, seems a suitable method for cooking insects. The findings indicate that, if optimally selected and cooked, edible insects can contribute significantly to the alleviation of protein, zinc, and iron deficiencies in target communities.